2010
DOI: 10.1111/j.1365-3156.2010.02697.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary tuberculosis in the West Bank, Palestinian Authority: molecular diagnostic approach

Abstract: Summaryobjective To compare the effectiveness and feasibility of an insertion sequence (IS6110)-based polymerase chain reaction (PCR) assay with conventional methods of detecting Mycobacterium tuberculosis and to analyse mutations present in the hot spot region of the RNA polymerase B subunit (rpoB) gene associated with rifampin resistance by DNA sequencing.methods Ninety-five sputum samples from 84 clinically suspected cases of tuberculosis were tested for mycobacterial infections by Ziehl Neelsen smear exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 32 publications
(64 reference statements)
0
11
0
3
Order By: Relevance
“…In those blood samples, smear microscopy and culture were positive in only 1 and 2 samples, respectively; this might be due to the small number of bacilli in the circulation. ( 6 , 7 ) In fact, the sensitivity of PCR in peripheral blood mononuclear cells, as used here, has been reported to be better than is that of culture, both having similar specificity. ( 11 , 16 , 29 ) In addition, clinical specimens, such as cerebrospinal fluid, blood, and sputum, have been described as good substrates for PCR( 26 ) with good concordance (kappa = 0.6867; p = 0.625; McNemar's test), as in our results, in which the level of positivity in extrapulmonary samples was higher when nested PCR was used (p = 0.0042), thus corroborating the findings of Noussair et al( 21 ) Different rates of sensitivity were described using the molecular methodology for this type of sample in studies conducted in France( 21 ) and India( 12 ) (86.6% and 90%, respectively).…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…In those blood samples, smear microscopy and culture were positive in only 1 and 2 samples, respectively; this might be due to the small number of bacilli in the circulation. ( 6 , 7 ) In fact, the sensitivity of PCR in peripheral blood mononuclear cells, as used here, has been reported to be better than is that of culture, both having similar specificity. ( 11 , 16 , 29 ) In addition, clinical specimens, such as cerebrospinal fluid, blood, and sputum, have been described as good substrates for PCR( 26 ) with good concordance (kappa = 0.6867; p = 0.625; McNemar's test), as in our results, in which the level of positivity in extrapulmonary samples was higher when nested PCR was used (p = 0.0042), thus corroborating the findings of Noussair et al( 21 ) Different rates of sensitivity were described using the molecular methodology for this type of sample in studies conducted in France( 21 ) and India( 12 ) (86.6% and 90%, respectively).…”
Section: Discussionmentioning
confidence: 72%
“…This false-negative result in a cerebrospinal fluid sample (Table 1) might be related to the absence of copies of the IS 6110 gene, as previously described in studies conducted in southeast Asia, Denmark, Tunisia, India, and Vietnam, indicating the need to incorporate additional targets, such as TRC4, in order to improve molecular detection. ( 7 , 10 ) However, to our knowledge, no study to date has reported the absence of this element in M. tuberculosis strains in Brazil, and various studies have reported that this sequence is the most sensitive in order to detect the M. tuberculosis complex. ( 9 , 17 ) Another factor could be the presence of molecular reaction inhibitors in up to 18.6% of extrapulmonary specimens.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some authors concluded that IS6110-based PCR could be used routinely in clinical laboratories for rapid detection of M. tuberculosis, in sputum samples allowing early diagnosis and treatment (Ereqat et al, 2011). Evaluation of in-house PCR showed that variability in sensitivity and specificity is high (Cho et al, 2007).…”
Section: Advantages Of Is6110 As Target Of the Mtbcmentioning
confidence: 99%